Collapsing Response of a Nonlinear Shear-Beam Building Model Excited by a Strong-Motion Pulse at Its Base - Hamid Abbasgholiha; Vlado Gičev; Mihailo D. Trifunac; Reza S. Jalali; Maria I. Todorovska (GeoHazards, 2023)
We present a simple nonlinear model of a shear-beam building that experiences large nonlinear deformations and collapse when excited by large pulses of strong earthquake ground motion. In this paper, we introduce the model and show that its properties can be selected to be consistent with the damage observed in a seven-story hotel in San Fernando Valley of the Los Angeles metropolitan area during the 1994 Northridge earthquake. We also show an example of excitation that leads to the collapse of the model. We illustrate the response only for a sequence of horizontal pulses. We will describe the response of the same model to horizontal, vertical, and rocking motions at its base, as well as for more general excitation by strong earthquake ground motion, in future papers.